Effect of heat treatment on the tensile properties of incrementally processed modified polylactide - Kozik, Bogdan; Dębski, Mariusz; Bąk, Piotr; Gontarz, Małgorzata; Zaborniak, Małgorzata (Polimery, 2021)
The article presents the results of strength tests in the form of a static tensile test on the INSTRON 5967 testing machine. Samples were made with the use of the Prusa i3 MK3 3D printer, by modeling with a plasticized material (FFF) made of ABS copolymer, polylactide and its modified variant. According to the information provided by the manufacturer, heat-treated modified polylactide has mechanical properties similar to ABS copolymer filament. The publication also discusses the method of manufacturing elements subjected to the tests, the heat treatment process, as well as changes in material properties as a result of this treatment. Based on the test results, it was found that the annealing process increased the proportion of the crystalline phase, which significantly improved the strength properties of the modified polylactide.